(untitled) (Research, Society and Development, 2017)
The teaching of physics concepts involves the construction of knowledge in the students’ minds. The aim of this article is to present a case report of teaching density and specific mass concepts in high school technical education classes. The study analyzes the results of the construction of methodology and development of a product so that teachers of Physics can give their students the construction of the concept of density of objects and the specific mass of the substances and perceive the different constitutions of the substances found in the Nature or even technologically prepared. The work was motivating with the students praising the obtained learning.